2015
DOI: 10.1093/jnci/djv095
|View full text |Cite
|
Sign up to set email alerts
|

Predicting High-Grade Cancer at Ten-Core Prostate Biopsy Using Four Kallikrein Markers Measured in Blood in the ProtecT Study

Abstract: Background:Many men with elevated prostate-specific antigen (PSA) levels in serum do not have aggressive prostate cancer and undergo unnecessary biopsy. Retrospective studies using cryopreserved serum suggest that four kallikrein markers can predict biopsy outcome.Methods:Free, intact and total PSA, and kallikrein-related peptidase 2 were measured in cryopreserved blood from 6129 men with elevated PSA (≥3.0ng/mL) participating in the prospective, randomized trial Prostate Testing for Cancer and Treatment. Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 31 publications
7
103
0
5
Order By: Relevance
“…test, and the four kallikrein (4K) score test are developed to reduce the number of unnecessary biopsies in men with a PSA between 2-10 ng/mL. Prospective multicentre studies demonstrated that both tests out-performed f/t PSA for PCa detection [23,24]. Nevertheless a formal comparison of these new tests is lacking.…”
Section: Classificationmentioning
confidence: 99%
“…test, and the four kallikrein (4K) score test are developed to reduce the number of unnecessary biopsies in men with a PSA between 2-10 ng/mL. Prospective multicentre studies demonstrated that both tests out-performed f/t PSA for PCa detection [23,24]. Nevertheless a formal comparison of these new tests is lacking.…”
Section: Classificationmentioning
confidence: 99%
“…2832 The 4-kallikrein panel was measured in 6129 men with elevated PSA undergoing biopsy in the ProtecT trial. 29 Performance of the base model including age and PSA was compared with that of the base model with %fPSA and the base model with the 4-kallikrein panel. The model incorporating the 4-kallikrein panel had an AUC of 0.820 for high-grade PCa (versus 0.799 and 0.738 for %fPSA and PSA models, respectively; p < 0.001).…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…The AUC for high-grade cancer was 0.82 for the four-kallikrein panel versus 0.74 for a model with PSA but without the other kallikreins 11 . The model developed in ProtecT was then externally validated in a prospective US cohort (n=1012) by an independent set of investigators 4 .…”
Section: Kscorementioning
confidence: 93%